The Effectiveness of Gaze-Contingent Control in Computer Games. (August 2015) - Orlov, Paul A.; Apraksin, Nikolay
Eye-tracking technology and gaze-contingent control in human–computer interaction have become an objective reality. This article reports on a series of eye-tracking experiments, in which we concentrated on one aspect of gaze–contingent interaction: Its effectiveness compared with mouse-based control in a computer strategy game. We propose a measure for evaluating the effectiveness of interaction based on "the time of recognition" the game unit. In this article, we use this measure to compare gaze- and mouse-contingent systems, and we present the analysis of the differences as a function of the number of game units. Our results indicate that performance of gaze–contingent interaction is typically higher than mouse manipulation in a visual searching task. When tested on 60 subjects, the results showed that the effectiveness of gaze-contingent systems over 1.5 times higher. In addition, we obtained that eye behavior stays quite stabile with or without mouse interaction.